Two-Mode Photon-Number Correlations Created by Measurement-Induced Nonlinearity - Meier, Torsten; Hoepker, Jan Philipp; Protte, Maximilian; Eigner, Christof; Silberhorn, Christine; Sharapova, Polina R.; Sperling, Jan; Bartley, Tim (Conference on Lasers and Electro-Optics: Applications and Technology)
We demonstrate theoretically and experimentally complex correlations in the photon numbers of two-mode quantum states using measurement-induced nonlinearity. For this, we combine the interference of coherent states and single photons with photon sub-traction.

DC Ionic Conductivity in KTP and Its Isomorphs: Properties, Methods for Suppression, and Its Connection to Gray Tracking - Padberg, Laura; Quiring, Viktor; Bocchini, Adriana; Santandrea, Matteo; Gerstmann, Uwe; Schmidt, Wolf Gero; Silberhorn, Christine; Eigner, Christof (Crystals)
We study the DC conductivity in potassium titanyl phosphate (KTiOPO4, KTP) and its isomorphs KTiOAsO4 (KTA) and Rb1%K99%TiOPO4 (RKTP) and introduce a method by which to reduce the overall ionic conductivity in KTP by a potassium nitrate treatment. Furthermore, we create so-called gray tracking in KTP and investigate the ionic conductivity in theses areas. A local unintended reduction of the ionic conductivity is observed in the gray-tracked regions, which also induce additional optical absorption in the material. We show that a thermal treatment in an oxygen-rich atmosphere removes the gray tracking and brings the ionic conductivity as well as the optical transmission back to the original level. These studies can help to choose the best material and treatment for specific applications.

Direct Measurement of Higher-Order Nonlinear Polarization Squeezing - Prasannan, Nidhin; Sperling, Jan; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Driven Gaussian quantum walks - Held, Philip; Engelkemeier, Melanie; De, Syamsundar; Barkhofen, Sonja; Sperling, Jan; Silberhorn, Christine (Physical Review A)
Quantum walks function as essential means to implement quantum simulators, allowing one to study complex and often directly inaccessible quantum processes in controllable systems. In this contribution, the notion of a driven Gaussian quantum walk is introduced. In contrast to typically considered quantum walks in optical settings, we describe the operation of the walk in terms of a nonlinear map rather than a unitary operation, e.g., by replacing a beam-splitter-type coin with a two-mode squeezer, being a process that is controlled and driven by a pump field. This opens previously unattainable possibilities for quantum walks that include nonlinear elements as core components of their operation, vastly extending their range of applications. A full framework for driven Gaussian quantum walks is developed, including methods to dynamically characterize nonlinear, quantum, and quantum-nonlinear effects. Moreover, driven Gaussian quantum walks are compared with their classically interfering and linear counterparts, which are based on classical coherence of light rather than quantum superpositions. In particular, the generation and boost of highly multimode entanglement, squeezing, and other quantum effects are studied over the duration of the nonlinear walk. Importantly, we prove the quantumness of the evolution itself, regardless of the input state. A scheme for an experimental realization is proposed. Furthermore, nonlinear properties of driven Gaussian quantum walks are explored, such as amplification that leads to an ever increasing number of correlated quantum particles, constituting a source of new walkers during the walk. Therefore, a concept for quantum walks is proposed that leads to—and even produces—directly accessible quantum phenomena, and that renders the quantum simulation of nonlinear processes possible.

General analytic theory of classical collinear three-wave mixing in a monolithic cavity - Santandrea, Matteo; Stefszky, Michael; Silberhorn, Christine (Journal of Optics)

Effects of coherence on temporal resolution - De, Syamsundar; Gil López, Jano; Brecht, Benjamin; Silberhorn, Christine; Sánchez-Soto, Luis L.; Hradil, Zdeněk; Řeháček, Jaroslav (Physical Review Research)
Keywords: General Engineering

Achieving the Ultimate Quantum Timing Resolution - Ansari, Vahid; Brecht, Benjamin; Gil-Lopez, Jano; Donohue, John M.; Řeháček, Jaroslav; Hradil, Zdeněk; Sánchez-Soto, Luis L.; Silberhorn, Christine (PRX Quantum)

Continuous variable multimode quantum states via symmetric group velocity matching - Roman-Rodriguez, V; Brecht, Benjamin; Srinivasan, K; Silberhorn, Christine; Treps, N; Diamanti, E; Parigi, V (New Journal of Physics)

Production of waveguides made of materials from the KTP family - Padberg, Laura; Eigner, Christof; Santandrea, Matteo; Silberhorn, Christine

Multimode integrated SU(1,1) interferometer - Ferreri, A.; Santandrea, Matteo; Stefszky, Michael; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine; Sharapova, Polina (Conference on Lasers and Electro-Optics)
We present a frequency multimode integrated SU (1,1) interferometer with a polarization converter and strong signal-idler photon correlations. Phase sensitivity below the shot noise limit is demonstrated, various filtering and seeding strategies are discussed.

The potential and global outlook of integrated photonics for quantum technologies - Pelucchi, Emanuele; Fagas, Giorgos; Aharonovich, Igor; Englund, Dirk; Figueroa, Eden; Gong, Qihuang; Hannes, Hübel; Liu, Jin; Lu, Chao-Yang; Matsuda, Nobuyuki; Pan, Jian-Wei; Schreck, Florian; et al. (Nature Reviews Physics)
Keywords: General Physics and Astronomy

Improved non-linear devices for quantum applications - Gil López, Jano; Santandrea, Matteo; Roland, Ganaël; Brecht, Benjamin; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Silberhorn, Christine (New Journal of Physics)

Universal compressive tomography in the time-frequency domain - Gil López, Jano; Teo, Yong Siah; De, Syamsundar; Brecht, Benjamin; Jeong, Hyunseok; Silberhorn, Christine; Sánchez-Soto, Luis L. (Optica)

Quantum optical coherence: From linear to nonlinear interferometers - Luo, Kai Hong; Santandrea, Matteo; Stefszky, Michael; Sperling, Jan; Massaro, Marcello; Ferreri, Alessandro; Sharapova, Polina; Herrmann, Harald; Silberhorn, Christine (Physical Review A)

Probing the topological Anderson transition with quantum walks - Bagrets, Dmitry; Kim, Kun Woo; Barkhofen, Sonja; De, Syamsundar; Sperling, Jan; Silberhorn, Christine; Altland, Alexander; Micklitz, Tobias (Physical Review Research)

Transient subdiffusion via disordered quantum walks - Geraldi, Andrea; De, Syamsundar; Laneve, Alessandro; Barkhofen, Sonja; Sperling, Jan; Mataloni, Paolo; Silberhorn, Christine (Physical Review Research)

Statistical Benchmarking of Scalable Photonic Quantum Systems - Tiedau, J.; Engelkemeier, M.; Brecht, Benjamin; Sperling, Jan; Silberhorn, Christine (Physical Review Letters)

Experimental entanglement characterization of two-rebit states - Prasannan, Nidhin; De, Syamsundar; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Non-Invasive Visualization of Ferroelectric Domain Structures on the Non-Polar y-Surface of KTiOPO4 via Raman Imaging - Brockmeier, Julian; Mackwitz, Peter Walter Martin; Rüsing, Michael; Eigner, Christof; Padberg, Laura; Santandrea, Matteo; Silberhorn, Christine; Zrenner, Artur; Berth, Gerhard (Crystals)
Potassium titanyl phosphate (KTP) is a nonlinear optical material with applications in high-power frequency conversion or quasi-phase matching in submicron period domain grids. A prerequisite for these applications is a precise control and understanding of the poling mechanisms to enable the fabrication of high-grade domain grids. In contrast to the widely used material lithium niobate, the domain growth in KTP is less studied, because many standard methods, such as selective etching or polarization microscopy, provides less insight or are not applicable on non-polar surfaces, respectively. In this work, we present results of confocal Raman-spectroscopy of the ferroelectric domain structure in KTP. This analytical method allows for the visualization of domain grids of the non-polar KTP y-face and therefore more insight into the domain-growth and -structure in KTP, which can be used for improved domain fabrication.

Interferometric method for determining the losses of spatially multi-mode nonlinear waveguides based on second harmonic generation - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (Optics Express)

Waveguide resonator with an integrated phase modulator for second harmonic generation - Stefszky, Michael; Santandrea, Matteo; vom Bruch, Felix; Krapick, S.; Eigner, Christof; Ricken, R.; Quiring, V.; Herrmann, Harald; Silberhorn, Christine (Optics Express)

Single-channel electronic readout of a multipixel superconducting nanowire single photon detector - Tiedau, Johannes; Schapeler, Timon; Anant, Vikas; Fedder, Helmut; Silberhorn, Christine; Bartley, Tim (Optics Express)
We present a time-over-threshold readout technique to count the number of activated pixels from an array of superconducting nanowire single photon detectors (SNSPDs). This technique places no additional heatload on the cryostat, and retains the intrinsic count rate of the time-tagger. We demonstrate proof-of-principle operation with respect to a four-pixel device. Furthermore, we show that, given some permissible error threshold, the number of pixels that can be reliably read out scales linearly with the intrinsic signal-to-noise ratio of the individual pixel response.
Keywords: Atomic and Molecular Physics; and Optics

Interferometric method for determining the losses of spatially multi-mode nonlinear waveguides based on second harmonic generation. - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (Optics Express)
The characterisation of loss in optical waveguides is essential in understanding the performance of these devices and their limitations. Whilst interferometric-based methods generally provide the best results for low-loss waveguides, they are almost exclusively used to provide characterization in cases where the waveguide is spatially single-mode. Here, we introduce a Fabry-Pérot-based scheme to estimate the losses of a nonlinear (birefringent or quasi-phase matched) waveguide at a wavelength where it is multi-mode. The method involves measuring the generated second harmonic power as the pump wavelength is scanned over the phase matching region. Furthermore, it is shown that this method allows one to infer the losses of different second harmonic spatial modes by scanning the pump field over the separated phase matching spectra. By fitting the measured phase matching spectra from different titanium indiffused lithium niobate waveguides to the model presented in this paper, it is shown that one can estimate the second harmonic losses of a single spatial-mode, at wavelengths where the waveguides are spatially multi-mode.
Keywords: Atomic and Molecular Physics; and Optics

Roadmap on quantum light spectroscopy - Mukamel, Shaul; Freyberger, Matthias; Schleich, Wolfgang; Bellini, Marco; Zavatta, Alessandro; Leuchs, Gerd; Silberhorn, Christine; Boyd, Robert W; Sánchez-Soto, Luis Lorenzo; Stefanov, André; Barbieri, Marco; Paterova, Anna; et al. (Journal of Physics B: Atomic, Molecular and Optical Physics)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics

Single-photon sources: Approaching the ideal through multiplexing - Meyer-Scott, Evan; Silberhorn, Christine; Migdall, Alan (Review of Scientific Instruments)
Keywords: Instrumentation

Distillation of squeezing using an engineered pulsed parametric down-conversion source - Dirmeier, Thomas; Tiedau, Johannes; Khan, Imran; Ansari, Vahid; Müller, Christian R.; Silberhorn, Christine; Marquardt, Christoph; Leuchs, Gerd (Optics Express)
Hybrid quantum information processing combines the advantages of discrete and continues variable protocols by realizing protocols consisting of photon counting and homodyne measurements. However, the mode structure of pulsed sources and the properties of the detection schemes often require the use of optical filters in order to combine both detection methods in a common experiment. This limits the efficiency and the overall achievable squeezing of the experiment. In our work, we use photon subtraction to implement the distillation of pulsed squeezed states originating from a genuinely spatially and temporally single-mode parametric down-conversion source in non-linear waveguides. Due to the distillation, we witness an improvement of 0.17 dB from an initial squeezing value of −1.648 ± 0.002 dB, while achieving a purity of 0.58, and confirm the non-Gaussianity of the distilled state via the higher-order cumulants. With this, we demonstrate the source’s suitability for scalable hybrid quantum network applications with pulsed quantum light.
Keywords: Atomic and Molecular Physics; and Optics

Spatially single mode photon pair source at 800 nm in periodically poled Rubidium exchanged KTP waveguides - Eigner, Christof; Padberg, Laura; Santandrea, Matteo; Herrmann, Harald; Brecht, Benjamin; Silberhorn, Christine (Optics Express)

Spatial entanglement and state engineering via four-photon Hong–Ou–Mandel interference - Ferreri, A; Ansari, V; Brecht, Benjamin; Silberhorn, Christine; Sharapova, Polina R. (Quantum Science and Technology)
Abstract The phenomenon of entanglement is the basis of quantum information and quantum communication processes. Entangled systems with a large number of photons are of great interest at present because they provide a platform for streaming technologies based on photonics. In this paper we present a device which operates with four-photons and based on the Hong–Ou–Mandel interference. The presented device allows to maximize the degree of spatial entanglement and generate the highly entangled four-dimensional Bell states. Furthermore, the use of the interferometer in different regimes leads to fast interference fringes in the coincidence probability with period of oscillations twice smaller than the pump wavelength. We have a good agreement between theoretical simulations and experimental results.
Keywords: Electrical and Electronic Engineering; Physics and Astronomy (miscellaneous); Materials Science (miscellaneous); Atomic and Molecular Physics; and Optics

Detector-Agnostic Phase-Space Distributions - Sperling, Jan; Phillips, D. S.; Bulmer, J. F. F; Thekkadath, G. S.; Eckstein, A.; Wolterink, T. A. W.; Lugani, J.; Nam, S. W.; Lita, A.; Gerrits, T.; Vogel, W.; Agarwal, G. S.; et al. (Physical Review Letters)

Quantum photonics with active feedback loops - Engelkemeier, M.; Lorz, L.; De, Syamsundar; Brecht, Benjamin; Dhand, I.; Plenio, M. B.; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Local Versus Global Two-Photon Interference in Quantum Networks - Nitsche, Thomas; De, Syamsundar; Barkhofen, Sonja; Meyer-Scott, Evan; Tiedau, Johannes; Sperling, Jan; Gábris, Aurél; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

Free and defect-bound (bi)polarons in LiNbO3: Atomic structure and spectroscopic signatures from ab initio calculations - Schmidt, Falko; Kozub, Agnieszka L.; Biktagirov, Timur; Eigner, Christof; Silberhorn, Christine; Schindlmayr, Arno; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)
Polarons in dielectric crystals play a crucial role for applications in integrated electronics and optoelectronics. In this work, we use density-functional theory and Green's function methods to explore the microscopic structure and spectroscopic signatures of electron polarons in lithium niobate (LiNbO3). Total-energy calculations and the comparison of calculated electron paramagnetic resonance data with available measurements reveal the formation of bound polarons at Nb_Li antisite defects with a quasi-Jahn-Teller distorted, tilted configuration. The defect-formation energies further indicate that (bi)polarons may form not only at Nb_Li antisites but also at structures where the antisite Nb atom moves into a neighboring empty oxygen octahedron. Based on these structure models, and on the calculated charge-transition levels and potential-energy barriers, we propose two mechanisms for the optical and thermal splitting of bipolarons, which provide a natural explanation for the reported two-path recombination of bipolarons. Optical-response calculations based on the Bethe-Salpeter equation, in combination with available experimental data and new measurements of the optical absorption spectrum, further corroborate the geometries proposed here for free and defect-bound (bi)polarons.

Understanding gray track formation in KTP: Ti^3+ centers studied from first principles - Bocchini, Adriana; Eigner, Christof; Silberhorn, Christine; Schmidt, Wolf Gero; Gerstmann, Uwe (Phys. Rev. Materials)

Characterisation of width-dependent diffusion dynamics in rubidium-exchanged KTP waveguides - Padberg, Laura; Santandrea, Matteo; Rüsing, Michael; Brockmeier, Julian; Mackwitz, Peter; Berth, Gerhard; Zrenner, Artur; Eigner, Christof; Silberhorn, Christine (Optics Express)

Improving SPDC single-photon sources via extended heralding and feed-forward control - Massaro, Marcello; Meyer-Scott, Evan; Montaut, Nicola; Herrmann, Harald; Silberhorn, Christine (New Journal of Physics)

Characterisation of fabrication inhomogeneities in Ti:LiNbO3 waveguides - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (New Journal of Physics)

Fabrication limits of waveguides in nonlinear crystals and their impact on quantum optics applications - Santandrea, Matteo; Stefszky, Michael; Ansari, Vahid; Silberhorn, Christine (New Journal of Physics)

Counter-propagating photon pair generation in a nonlinear waveguide - Luo, Kai-Hong; Ansari, Vahid; Massaro, Marcello; Santandrea, Matteo; Eigner, Christof; Ricken, Raimund; Herrmann, Harald; Silberhorn, Christine (Optics Express)

Engineering integrated photon pair sources and multiplexed detectors (Conference Presentation) - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Eigner, Christof; Harder, Georg; Sansoni, Linda; Nitsche, Thomas; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; et al. (Advances in Photonics of Quantum Computing, Memory, and Communication XII)

Herstellung von Wellenleitern aus Materialien der KTP-Familie - Padberg, Laura; Eigner, Christof; Santandrea, Matteo; Silberhorn, Christine

Efficient C-band single-photon upconversion with chip-scale Ti-indiffused pp-LiNbO3 waveguides - Xie, Zhenda; Luo, Kai Hong; Chang, Kai Chi; Panoiu, Nicolae C.; Herrmann, Harald; Silberhorn, Christine; Wong, Chee Wei (Applied Optics)
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Estimating the Indistinguishability of Heralded Single Photons Using Second-Order Correlation - Faruque, Imad I.; Sinclair, Gary F.; Bonneau, Damien; Ono, Takafumi; Silberhorn, Christine; Thompson, Mark G.; Rarity, John G. (Physical Review Applied)
Keywords: General Physics and Astronomy

Temporally multimode four-photon Hong-Ou-Mandel interference - Ferreri, Alessandro; Ansari, V.; Silberhorn, Christine; Sharapova, Polina R. (Physical Review A)

Mode-independent quantum entanglement for light - Sperling, Jan; Perez-Leija, Armando; Busch, Kurt; Silberhorn, Christine (Physical Review A)

Experimental Reconstruction of Entanglement Quasiprobabilities - Sperling, Jan; Meyer-Scott, E.; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)

Engineering integrated sources of entangled photon pairs - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Harder, Georg; Sansoni, Linda; Herrmann, Harald; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; Barkhofen, Sonja; et al. (Frontiers in Optics / Laser Science)

Engineering integrated sources of entangled photon pairs - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Harder, Georg; Sansoni, Linda; Herrmann, Harald; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Bartley, Tim J.; Barkhofen, Sonja; et al. (Frontiers in Optics / Laser Science)

High-performance source of spectrally pure, polarization entangled photon pairs based on hybrid integrated-bulk optics - Meyer-Scott, Evan; Prasannan, Nidhin; Eigner, Christof; Quiring, Viktor; Donohue, John M.; Barkhofen, Sonja; Silberhorn, Christine (Optics Express)

High-power waveguide resonator second harmonic device with external conversion efficiency up to 75% - Stefszky, Michael; Ricken, R; Eigner, Christof; Quiring, V; Herrmann, Harald; Silberhorn, Christine (Journal of Optics)

Compressive characterization of telecom photon pairs in the spatial and spectral degrees of freedom - Montaut, Nicola; Magaña-Loaiza, Omar S.; Bartley, Tim; Verma, Varun B.; Nam, Sae Woo; Mirin, Richard P.; Silberhorn, Christine; Gerrits, Thomas (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Streak camera imaging of single photons at telecom wavelength - Allgaier, Markus; Ansari, Vahid; Eigner, Christof; Quiring, Viktor; Ricken, Raimund; Donohue, John Matthew; Czerniuk, Thomas; Aßmann, Marc; Bayer, Manfred; Brecht, Benjamin; Silberhorn, Christine (Applied Physics Letters)

Quantum-Limited Time-Frequency Estimation through Mode-Selective Photon Measurement - Donohue, J. M.; Ansari, V.; Řeháček, J.; Hradil, Z.; Stoklasa, B.; Paúr, M.; Sánchez-Soto, L. L.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Manipulation of Two-Photon Interference by Entanglement - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Silberhorn, Christine; Meier, Torsten (Conference on Lasers and Electro-Optics)

Incomplete Detection of Nonclassical Phase-Space Distributions - Bohmann, M.; Tiedau, J.; Bartley, Tim; Sperling, Jan; Silberhorn, Christine; Vogel, W. (Physical Review Letters)

Monolithically Integrated Hong-Ou-Mandel Experiment in LiNbO3 - Luo, Kai Hong; Brauner, Sebastian; Eigner, Christof; Sharapova, Polina; Ricken, Raimund; Meier, Torsten; Herrmann, Harald; Silberhorn, Christine (Conference on Lasers and Electro-Optics)

Imaging of 180∘ ferroelectric domain walls in uniaxial ferroelectrics by confocal Raman spectroscopy: Unraveling the contrast mechanism - Rüsing, Michael; Neufeld, Sergej; Brockmeier, Julian; Eigner, Christof; Mackwitz, P.; Spychala, K.; Silberhorn, Christine; Schmidt, Wolf Gero; Berth, Gerhard; Zrenner, Artur; Sanna, S. (Physical Review Materials)
In recent years, Raman spectroscopy has been used to visualize and analyze ferroelectric domain structures. The technique makes use of the fact that the intensity or frequency of certain phonons is strongly influenced by the presence of domain walls. Although the method is used frequently, the underlying mechanism responsible for the changes in the spectra is not fully understood. This inhibits deeper analysis of domain structures based on this method. Two different models have been proposed. However, neither model completely explains all observations. In this work, we have systematically investigated domain walls in different scattering geometries with Raman spectroscopy in the common ferroelectric materials used in integrated optics, i.e., KTiOPO4, LiNbO3, and LiTaO3. Based on the two models, we can demonstrate that the observed contrast for domain walls is in fact based on two different effects. We can identify on the one hand microscopic changes at the domain wall, e.g., strain and electric fields, and on the other hand a macroscopic change of selection rules at the domain wall. While the macroscopic relaxation of selection rules can be explained by the directional dispersion of the phonons in agreement with previous propositions, the microscopic changes can be explained qualitatively in terms of a simplified atomistic model.

Fabrication of low-loss Rb-exchanged ridge waveguides in z-cut KTiOPO_4 - Volk, Martin F.; Rüter, Christian E.; Santandrea, Matteo; Eigner, Christof; Padberg, Laura; Herrmann, Harald; Silberhorn, Christine; Kip, Detlef (Optical Materials Express)

A monolithic, doubly-resonant parametric down-conversion source for Caesium Raman memories - Brecht, Benjamin; Lazo-Arjona, O.; Kaczmarek, K. T.; Parker, T.; Ricken, R.; Quiring, V.; Eigner, Christof; Luo, K. H.; Herrmann, Harald; Silberhorn, Christine; Walmsley, I. A. (Frontiers in Optics 2017)

Waveguide Cavity Resonator as a Source of Optical Squeezing - Stefszky, M.; Ricken, R.; Eigner, Christof; Quiring, V.; Herrmann, Harald; Silberhorn, Christine (Physical Review Applied)

A two-channel, spectrally degenerate polarization entangled source on chip - Sansoni, Linda; Luo, Kai Hong; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (npj Quantum Information)

Identifying and Realizing Symmetries in Quantum Walks - Symmetry Classes and Quantum Walks - Schütte, Philipp

Limits of the time-multiplexed photon-counting method - Kruse, Regina; Tiedau, Johannes; Bartley, Tim; Barkhofen, Sonja; Silberhorn, Christine (Physical Review A)

Driven Boson Sampling - Barkhofen, Sonja; Bartley, Tim; Sansoni, Linda; Kruse, Regina; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

High-Efficiency Plug-and-Play Source of Heralded Single Photons - Montaut, Nicola; Sansoni, Linda; Meyer-Scott, Evan; Ricken, Raimund; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (Physical Review Applied)
Keywords: General Physics and Astronomy

Extracting the physical sector of quantum states - Mogilevtsev, D; Teo, Y S; Řeháček, J; Hradil, Z; Tiedau, J; Kruse, R; Harder, G; Silberhorn, Christine; Sanchez-Soto, L L (New Journal of Physics)
Keywords: General Physics and Astronomy

Harnessing temporal modes for multi-photon quantum information processing based on integrated optics - Harder, G.; Ansari, V.; Bartley, Tim; Brecht, Benjamin; Silberhorn, Christine (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences)
In the last few decades, there has been much progress on low loss waveguides, very efficient photon-number detectors and nonlinear processes. Engineered sum-frequency conversion is now at a stage where it allows operation on arbitrary temporal broadband modes, thus making the spectral degree of freedom accessible for information coding. Hereby the information is often encoded into the temporal modes of a single photon. Here, we analyse the prospect of using multi-photon states or squeezed states in different temporal modes based on integrated optics devices. We describe an analogy between mode-selective sum-frequency conversion and a network of spatial beam splitters. Furthermore, we analyse the limits on the achievable squeezing in waveguides with current technology and the loss limits in the conversion process. This article is part of the themed issue ‘Quantum technology for the 21st century’.

Fast time-domain measurements on telecom single photons - Allgaier, Markus; Vigh, Gesche; Ansari, Vahid; Eigner, Christof; Quiring, Viktor; Ricken, Raimund; Brecht, Benjamin; Silberhorn, Christine (Quantum Science and Technology)

Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (New Journal of Physics)

Modified two-photon interference achieved by the manipulation of entanglement - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Silberhorn, Christine; Meier, Torsten (Physical Review A)

Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (New Journal of Physics)

Towards integrated superconducting detectors on lithium niobate waveguides - Höpker, Jan Philipp; Bartnick, Moritz; Meyer-Scott, Evan; Thiele, Frederik; Meier, Torsten; Bartley, Tim; Krapick, Stephan; Montaut, Nicola M.; Santandrea, Matteo; Herrmann, Harald; Lengeling, Sebastian; Ricken, Raimund; et al. (Quantum Photonic Devices)

Quantum technology: from research to application - Schleich, Wolfgang P.; Ranade, Kedar S.; Anton, Christian; Arndt, Markus; Aspelmeyer, Markus; Bayer, Manfred; Berg, Gunnar; Calarco, Tommaso; Fuchs, Harald; Giacobino, Elisabeth; Grassl, Markus; Hänggi, Peter; et al. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

In-lab ALOHA mid-infrared up-conversion interferometer with high fringe contrast @λ = 3.39 μm - Szemendera, L.; Darré, P.; Baudoin, R.; Grossard, L.; Delage, L.; Herrmann, Harald; Silberhorn, Christine; Reynaud, F. (Monthly Notices of the Royal Astronomical Society)
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Local Sampling of the Wigner Function at Telecom Wavelength with Loss-Tolerant Detection of Photon Statistics - Harder, G.; Silberhorn, Christine; Rehacek, J.; Hradil, Z.; Motka, L.; Stoklasa, B.; Sánchez-Soto, L. L. (Physical Review Letters)
Keywords: General Physics and Astronomy

Identification of ferroelectric domain structure sensitive phonon modes in potassium titanyl phosphate: A fundamental study - Rüsing, Michael; Eigner, Christof; Mackwitz, P.; Berth, Gerhard; Silberhorn, Christine; Zrenner, Artur (Journal of Applied Physics)
Confocal Raman spectroscopy is applied to identify ferroelectric domain structure sensitive phonon modes in potassium titanyl phosphate. Therefore, polarization-dependent measurements in various scattering configurations have been performed to characterize the fundamental Raman spectra of the material. The obtained spectra are discussed qualitatively based on an internal mode assignment. In the main part of this work, we have characterized z-cut periodically poled potassium titanyl phosphate in terms of polarity- and structure-sensitive phonon modes. Here, we find vibrations whose intensities are linked to the ferroelectric domain walls. We interpret this in terms of changes in the polarizability originating from strain induced by domain boundaries and the inner field distribution. Hence, a direct and 3D visualization of ferroelectric domain structures becomes possible in potassium titanyl phosphate.

Storage of hyperentanglement in a solid-state quantum memory - Tiranov, Alexey; Lavoie, Jonathan; Ferrier, Alban; Goldner, Philippe; Verma, Varun B.; Nam, Sae Woo; Mirin, Richard P.; Lita, Adriana E.; Marsili, Francesco; Herrmann, Harald; Silberhorn, Christine; Gisin, Nicolas; et al. (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Liquid-nitrogen cooled, free-running single-photon sensitive detector at telecommunication wavelengths - Covi, M.; Pressl, B.; Günthner, T.; Laiho, K.; Krapick, Stefan; Silberhorn, Christine; Weihs, G. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

Uncovering Quantum Correlations with Time-Multiplexed Click Detection - Sperling, Jan; Bohmann, M.; Vogel, W.; Harder, G.; Brecht, Benjamin; Ansari, V.; Silberhorn, Christine (Physical Review Letters)

Resonance chains in open systems, generalized zeta functions and clustering of the length spectrum - Barkhofen, Sonja; Faure, F; Weich, Tobias (Nonlinearity)
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Real-time coherent detection of phase modulated ultrashort pulses after time-to-space conversion and spatial demultiplexing - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Time-multiplexed measurements of nonclassical light at telecom wavelengths - Harder, G.; Silberhorn, Christine; Rehacek, J.; Hradil, Z.; Motka, L.; Stoklasa, B.; Sánchez-Soto, L. L. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Quantum teleportation from a telecom-wavelength photon to a solid-state quantum memory - Bussières, Félix; Clausen, Christoph; Tiranov, Alexey; Korzh, Boris; Verma, Varun B.; Nam, Sae Woo; Marsili, Francesco; Ferrier, Alban; Goldner, Philippe; Herrmann, Harald; Silberhorn, Christine; Sohler, Wolfgang; et al. (Nature Photonics)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

A source of polarization-entangled photon pairs interfacing quantum memories with telecom photons - Clausen, C; Bussières, F; Tiranov, A; Herrmann, Harald; Silberhorn, Christine; Sohler, W; Afzelius, M; Gisin, N (New Journal of Physics)
Keywords: General Physics and Astronomy

Generation of Nonclassical Biphoton States through Cascaded Quantum Walks on a Nonlinear Chip - Solntsev, Alexander S.; Setzpfandt, Frank; Clark, Alex S.; Wu, Che Wen; Collins, Matthew J.; Xiong, Chunle; Schreiber, Andreas; Katzschmann, Fabian; Eilenberger, Falk; Schiek, Roland; Sohler, Wolfgang; Mitchell, Arnan; et al. (Physical Review X)
Keywords: General Physics and Astronomy

Full-field reconstruction of ultrashort waveforms by time to space conversion interferogram analysis - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Tomography by Noise - Harder, G.; Mogilevtsev, D.; Korolkova, N.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Driven Quantum Walks - Hamilton, Craig S.; Kruse, Regina; Sansoni, Linda; Silberhorn, Christine; Jex, Igor (Physical Review Letters)
Keywords: General Physics and Astronomy

Efficient algorithm for optimizing data-pattern tomography - Motka, L.; Stoklasa, B.; Rehacek, J.; Hradil, Z.; Karasek, V.; Mogilevtsev, D.; Harder, G.; Silberhorn, Christine; Sánchez-Soto, L. L. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Theory of filtered type-II parametric down-conversion in the continuous-variable domain: Quantifying the impacts of filtering - Christ, Andreas; Lupo, Cosmo; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (Physical Review A)
Parametric down-conversion (PDC) forms one of the basic building blocks for quantum optical experiments. However, the intrinsic multimode spectral-temporal structure of pulsed PDC often poses a severe hindrance for the direct implementation of the heralding of pure single-photon states or, for example, continuous-variable entanglement distillation experiments. To get rid of multimode effects narrowband frequency filtering is frequently applied to achieve a single-mode behavior. A rigorous theoretical description to accurately describe the effects of filtering on PDC, however, is still missing. To date, the theoretical models of filtered PDC are rooted in the discrete-variable domain and only account for filtering in the low-gain regime, where only a few photon pairs are emitted at any single point in time. In this paper we extend these theoretical descriptions and put forward a simple model, which is able to accurately describe the effects of filtering on PDC in the continuous-variable domain. This developed straightforward theoretical framework enables us to accurately quantify the tradeoff between suppression of higher-order modes, reduced purity, and lowered Einstein–Podolsky–Rosen entanglement, when narrowband filters are applied to multimode type-II PDC.

Experimental Observation of the Spectral Gap in Microwave n-Disk Systems - Barkhofen, Sonja; Weich, Tobias; Potzuweit, A.; Stöckmann, H.-J.; Kuhl, U.; Zworski, M. (Physical Review Letters)
Keywords: General Physics and Astronomy

Time-to-space conversion of ultrafast waveforms at 155 μm in a planar periodically poled lithium niobate waveguide - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Post-selection free, integrated optical source of non-degenerate, polarization entangled photon pairs - Herrmann, Harald; Yang, Xu; Thomas, Abu; Poppe, Andreas; Sohler, Wolfgang; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef U.; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Silberhorn, Christine; Leuchs, Gerd; Marquardt, Christoph (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Increasing the Dimensionality of Quantum Walks Using Multiple Walkers - Rohde, Peter P.; Schreiber, Andreas; Štefaňák, Martin; Jex, Igor; Gilchrist, Alexei; Silberhorn, Christine (Journal of Computational and Theoretical Nanoscience)
Keywords: Electrical and Electronic Engineering; Computational Mathematics; Condensed Matter Physics; General Materials Science; General Chemistry

Spatio-spectral characteristics of parametric down-conversion in waveguide arrays - Kruse, R; Katzschmann, F; Christ, A; Schreiber, A; Wilhelm, S; Laiho, K; Gábris, A; Hamilton, C S; Jex, I; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

A 2D Quantum Walk Simulation of Two-Particle Dynamics - Schreiber, Andreas; Gábris, Aurél; Rohde, Peter P.; Laiho, Kaisa; Štefaňák, Martin; Potoček, Václav; Hamilton, Craig; Jex, Igor; Silberhorn, Christine (Science)
Here, There, Everywhere Random walks are a powerful mathematical method that can be used to simulate certain processes in biology, chemistry, or even the stock market. They present a statistical method for mapping the possible routes that processes can take. Quantum walks are expected to be able to probe multiple paths simultaneously. Quantum walks have been demonstrated for one-dimensional, or straight-line, walks. Now, Schreiber et al. (p. 55 , published online 8 March) demonstrate an optical system that can simulate quantum walks over a two-dimensional system, thereby providing the capability of describing much more complex processes.
Keywords: Multidisciplinary

Limits on the deterministic creation of pure single-photon states using parametric down-conversion - Christ, Andreas; Silberhorn, Christine (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

High resolution time-to-space conversion of sub-picosecond pulses at 155µm by non-degenerate SFG in PPLN crystal - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Exponentially enhanced quantum communication rate by multiplexing continuous-variable teleportation - Christ, Andreas; Lupo, Cosmo; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Characteristics of displaced single photons attained via higher order factorial moments - Laiho, Kaisa; Avenhaus, Malte; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy